A high heat-resistant and low-friction wollastonite fiber-modified polytetrafluoroethylene lubricating material and preparation method thereof
By adding a small amount of lubricating filler to the wollastonite fiber/Polytetrafluoroethylene composite material and adopting a specific process flow, the orientation arrangement of wollastonite fibers is solved, and the high friction coefficient and heat resistance of the composite material under high temperature conditions are solved. The problem of insufficient sexuality achieves higher heat resistance and dimensional stability.
Patent Information
- Application Number
- CN202311375060.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-23
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-10-23
AI Technical Summary
The existing wollastonite fiber/Polytetrafluoroethylene composite lubricating materials have high friction coefficient and insufficient heat resistance, resulting in dimensional changes and lubrication failure under high temperature conditions, and the process flow is complicated.
Polytetrafluoroethylene resin is used as the polymer matrix, wollastonite fiber is the main reinforcement filler, combined with a small amount of lubricating filler, it is prepared through mechanical blending, pre-pressing, sintering molding, turning and drafting forming processes to optimize the wollastonite fibers. Oriented arrangement reduces friction coefficient and improves heat resistance.
It significantly reduces the friction coefficient, improves heat resistance and dimensional stability, improves the mechanical strength, tribological properties and thermal conductivity of the material, and is suitable for precision lubricating components in high-tech fields.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to a modified polytetrafluoroethylene lubricating material, in particular to a polytetrafluoroethylene lubricating material modified with wollastonite fiber, which is mainly used for manufacturing sealing or bearing components and belongs to the field of sealing materials or bearing materials. Background Art
[0002] Polytetrafluoroethylene is widely used in the processing and manufacturing of sealing elements and bearing components due to its excellent corrosion resistance, aging resistance and self-lubricating properties. However, its accelerated creep and wear at high temperatures limit its wider application. Introducing various functional fillers into the polytetrafluoroethylene resin matrix for composite modification is the most widely used reinforcement method. Among them, fibrous fillers are often used as the main polytetrafluoroethylene reinforcement fillers due to their high aspect ratio, good load-bearing capacity, wear resistance and thermal stability.
[0003] Wollastonite fiber is a metasilicate mineral, and its microstructure is usually needle-like fiber with a very high aspect ratio. It can effectively improve the dimensional stability, wear resistance and heat resistance of polytetrafluoroethylene materials, especially it can effectively avoid dimensional changes and lubrication failure caused by ambient temperature or friction heating. A well-known foreign sealing manufacturer uses wollastonite fiber to modify polytetrafluoroethylene, and has achieved industrialization of the product, which has been successfully applied to some commercial and military aircraft overseas. However, in actual engineering applications, there are also some unresolved problems in the modification of polytetrafluoroethylene with wollastonite fiber, mainly manifested in the disadvantages of wollastonite fiber itself, such as short and brittle, poor flexibility, and high hardness; at the same time, due to its unique needle-like structure, after the introduction of polytetrafluoroethylene matrix, it often leads to an increase in friction coefficient and even friction noise. Therefore, in the existing composite system, the content of wollastonite fiber is often limited, and it is difficult to give full play to its unique advantages of low thermal expansion rate and strong heat shock resistance. It is often necessary to use the interface modification method to treat the wollastonite fiber, resulting in a lengthy and cumbersome process. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a high heat-resistant and low-friction wollastonite fiber modified polytetrafluoroethylene lubricating material in view of the bottleneck of the existing wollastonite fiber / polytetrafluoroethylene composite lubricating material having high friction coefficient and insufficient heat resistance.
[0005] 1. Preparation of wollastonite fiber modified polytetrafluoroethylene lubricating material
[0006] The present invention uses polytetrafluoroethylene resin as the polymer matrix, wollastonite fiber as the main reinforcing filler, and a small amount of lubricating filler as the modified component, and is prepared through mechanical blending, pre-pressing, sintering, turning and drawing shaping processes. The specific raw material ratio and preparation process are as follows:
[0007] Raw material components: by weight, 75-89 parts of polytetrafluoroethylene resin, 10-20 parts of wollastonite fiber, and 1-5 parts of lubricating filler. Among the raw material components, the particle size of polytetrafluoroethylene resin is 20-80μm, and the tensile strength is 25-40MPa; the wollastonite fiber is needle-shaped, with a thick end diameter of 0.5-10μm and a length of 10-200μm; the lubricating filler is one or more of molybdenum disulfide, silicon dioxide, graphite, and graphite fluoride; the size of the lubricating filler is 0.02-80μm.
[0008] In terms of the raw material component design of the composite material of the present invention, wollastonite fiber has stable chemical properties, low thermal expansion coefficient, high melting point, and excellent heat shock resistance. After being compounded with a polytetrafluoroethylene matrix, the heat resistance and dimensional stability of the composite material can be effectively improved; combined with a small amount of lubricating filler, the wear resistance can be further improved, and the adverse effect of wollastonite fiber on the friction coefficient can be preliminarily reduced, thereby comprehensively improving the mechanical strength, tribological properties, thermal conductivity and dimensional stability of the polytetrafluoroethylene composite material.
[0009] Preparation process: including the following steps:
[0010] (1) Mechanical blending: Place polytetrafluoroethylene resin, wollastonite fiber and lubricating filler in a mechanical mixer and mix them evenly to obtain a mixed material. Mechanical blending is carried out in a three-axis mixer, the shearing knife speed in the mixing kettle is 5-40 rpm, the mixing kettle as a whole revolves around the cantilever at a speed of 10-50 rpm, the rotation speed is 2-10 rpm, and the mixing time is 3-15 min.
[0011] (2) Pre-pressing: Place the mixed material in a molding machine and press it at a pressure of 35-60 MPa to obtain a pre-pressed blank. During pre-pressing, the pressing rate is 0.5-10 mm / min and the holding time is 5-30 min. The obtained pre-pressed blank is in the shape of a rod with a diameter of 10-120 mm and a length of 30-500 mm.
[0012] (3) Sintering: The pre-pressed blank is sintered in nitrogen or air at 360-380°C for 15-200 min to obtain a sintered blank. The sintering is carried out in a special PTFE sintering furnace equipped with a rotating tray, and the tray speed is controlled to be 5-20 rpm.
[0013] (4) Turning: Use hard stainless steel, silicon carbide ceramic or diamond tools to turn the sintered blank to obtain a turning strip. The feed rate of turning is 0.01~0.05mm / r, the spindle speed is 600~3000rpm, and the dwell time is 2~600s. The thickness of the turning strip is 0.5~15mm.
[0014] (5) Drawing and shaping: The turned strip is drawn at a temperature of 60 to 120°C and a drawing strain of 0.5 to 5% for 60 to 900 seconds, and after cooling, wollastonite fiber / polytetrafluoroethylene composite lubricating material is obtained.
[0015] In terms of preparation technology, the present invention ensures the performance and dimensional precision of the composite material through pre-pressing, sintering, turning and stretching shaping process and parameter control. In particular, the stretching shaping process is used to promote the directional arrangement of needle-shaped wollastonite fibers, thereby solving the problem of excessively high friction coefficient of the composite material caused by the short and brittle wollastonite fibers and poor flexibility.
[0016] 2. Performance test of wollastonite fiber modified polytetrafluoroethylene lubricating material
[0017] 1. Friction and wear performance test
[0018] Test method: According to ASTM G99-05, the obtained polytetrafluoroethylene lubricating material molded product is processed into a block sample with a size of 19mm×12mm×12mm, matched with a 316 stainless steel ring, and tested in an MRH-3 high-speed ring block friction and wear tester; the test contact load is 200N, the linear speed is 0.5m / s, and the running time is 30min; the friction coefficient is automatically recorded and output by the tester, and the wear rate is calculated by the mass loss before and after the sample is worn. The sample is placed in a constant temperature and humidity chamber, placed in 130℃ hot air for 72h, and its friction and wear performance is tested again. The degree of friction and wear performance attenuation is expressed as a percentage of the measured friction coefficient and wear rate to the corresponding values of the unaged sample.
[0019] Test results: The friction coefficient of the wollastonite fiber modified polytetrafluoroethylene bearing lubricating material prepared by the present invention is 0.02~0.10, and the wear rate is (1.0~5.0) ×10 -5 mm 3 / Nm. After being placed in 130℃ hot air for 72h, the friction coefficient changed to +0.5%~+5%, and the wear rate changed to +1%~+7%. It can be seen that the wollastonite fiber modified polytetrafluoroethylene lubricating material has excellent friction coefficient and wear rate, and the friction and wear performance of the material only slightly decays after aging under 130℃ hot air conditions.
[0020] 2. Tensile strength test
[0021] Test method: The polytetrafluoroethylene lubricating material is machined into the size specified by the national standard and tested on a universal testing machine for mechanical properties. The tensile strength specimen is a dumbbell of 80 mm×10 mm×4 mm. The test standard is GB / T1040.2-2006, and the tensile rate is 100 mm / min. The specimen is placed in a constant temperature and humidity chamber and placed in hot air at 130°C for 72 hours, and its friction and wear performance is tested again. The degree of friction and wear performance attenuation is expressed as a percentage of the corresponding values of the unaged specimen with the measured friction coefficient and wear rate.
[0022] Test results: The wollastonite fiber modified polytetrafluoroethylene bearing lubricating material prepared by the present invention has a tensile strength of 25-35 MPa. After being placed in 130°C hot air for 72 hours, the tensile strength changes to -2%-5%. It can be seen that the wollastonite fiber modified polytetrafluoroethylene lubricating material has excellent tensile strength, and the tensile strength of the material only slightly decays after aging under 130°C hot air conditions.
[0023] 3. Dimensional stability test
[0024] Test method: The polytetrafluoroethylene lubricating material is machined into a disc with a diameter of 30mm and a height of 0.2mm, and its diameter is measured with a vernier caliper. The sample is placed in a constant temperature and humidity chamber, placed in hot air at 130℃ for 72 hours, and its diameter is tested again. The degree of friction and wear performance attenuation is expressed as a percentage of the measured diameter value to the corresponding value of the unaged sample.
[0025] Test results: After the wollastonite fiber modified polytetrafluoroethylene bearing lubricating material prepared by the present invention was placed in 130°C hot air for 72 hours, the diameter changed by +0.05% to +0.20%. It can be seen that the wollastonite fiber modified polytetrafluoroethylene lubricating material has excellent dimensional stability.
[0026] In summary, the composite material prepared by the present invention using polytetrafluoroethylene resin as a polymer matrix, wollastonite fiber as a main reinforcing filler, and a small amount of lubricating filler as a modified component through mechanical blending, pre-pressing, sintering molding, turning and drawing shaping processes has good mechanical strength, tribological properties, thermal conductivity and dimensional stability, is suitable for manufacturing precision lubricating parts in high-tech fields such as aerospace and marine engineering, such as sealing elements and bearing parts, and has the comprehensive advantages of high heat resistance, low friction, high wear resistance and high dimensional accuracy. DETAILED DESCRIPTION
[0027] The preparation method and properties of the wollastonite fiber modified polytetrafluoroethylene lubricating material of the present invention are further described below through specific examples.
[0028] Example 1
[0029] (1) Mechanical blending: 800 g of polytetrafluoroethylene resin (particle size 60 μm, tensile strength 35 MPa), 150 g of wollastonite fiber (needle-shaped, thick end diameter 5 μm, length 38 μm), and 50 g of molybdenum disulfide (size 50 μm) were placed in a three-axis mixer and mixed for 5 min. The shearing tool speed of the mixer was 5 rpm, the overall revolution speed of the mixer around the cantilever was 10 rpm, and the rotation speed was 8 rpm;
[0030] (2) Pre-pressing: Take 623 g of the blended raw material, add it into a steel mold with a diameter of 60 mm, place it on the platform of the molding machine, pressurize it to 40 MPa at a rate of 1 mm / min, and maintain it for 10 minutes. A rod-shaped pre-pressed blank with a diameter of 60 mm and a height of 30 mm is obtained;
[0031] (3) Sintering: Place the blank into a special PTFE sintering machine equipped with a rotating tray, use a nitrogen atmosphere, sinter at a temperature of 375°C, for 60 minutes, and a tray speed of 20 rpm;
[0032] (4) Turning: Install a hard stainless steel tool, start and adjust the spindle speed to 600 rpm, and then turn the sintered blank at a feed rate of 0.05 mm / r with a dwell time of 60 s;
[0033] (5) Drafting and shaping: The processed turning belt with a width of 30 mm, a thickness of 15 mm, and a length of 50 mm was flattened and placed in a constant temperature and humidity chamber, the temperature was set to 60°C, the drafting distance was set to 25 mm (5% drafting strain), and maintained for 600 seconds. After being taken out and cooled, the wollastonite fiber modified polytetrafluoroethylene lubricating material was obtained. The properties of the polytetrafluoroethylene lubricating material are shown in Table 1.
[0034] Example 2
[0035] (1) Mechanical blending: 750 g of polytetrafluoroethylene resin (particle size 50 μm, tensile strength 40 MPa), 200 g of wollastonite fiber (needle-shaped, thick end diameter 7 μm, length 150 μm), and 50 g of silica (size 0.05 μm) were placed in a three-axis mixer and mixed for 10 min. The shearing tool speed of the mixer was 10 rpm, the overall revolution speed of the mixer around the cantilever was 40 rpm, and the rotation speed was 5 rpm;
[0036] (2) Pre-pressing: Take 275.5 g of the blended raw material, add it into a steel mold with a diameter of 100 mm, place it on the platform of the molding machine, pressurize it to 55 MPa at a rate of 5 mm / min, and maintain it for 15 minutes. A rod-shaped pre-pressed blank with a diameter of 100 mm and a height of 15 mm is obtained;
[0037] (3) Sintering: Place the blank into a special PTFE sintering machine equipped with a rotating tray, use air atmosphere, sinter at a temperature of 380°C, for 40 minutes, and a tray speed of 10 rpm;
[0038] (4) Turning: Install a hard stainless steel tool, start and adjust the spindle speed to 750 rpm, and then turn the sintered blank at a feed rate of 0.01 mm / r with a dwell time of 120 s;
[0039] (5) Drafting and shaping: The processed turning belt with a width of 15 mm, a thickness of 5 mm and a length of about 20 m was flattened, and a section of 500 mm was placed in a constant temperature and humidity chamber, the temperature was set to 80 ° C, the drafting distance was set to 5 mm (1% drafting strain), and maintained for 60 seconds. After being taken out and cooled, the wollastonite fiber modified polytetrafluoroethylene lubricating material was obtained. The properties of the polytetrafluoroethylene lubricating material are shown in Table 1.
[0040] Example 3
[0041] (1) Mechanical blending: 890 g of polytetrafluoroethylene resin (particle size 20 μm, tensile strength 38 MPa), 100 g of wollastonite fiber (needle-shaped, thick end diameter 10 μm, length 200 μm), and 10 g of fluorinated graphite (size 75 μm) were placed in a three-axis mixer and mixed for 3 min. The shearing tool speed of the mixer was 8 rpm, the overall revolution speed of the mixer around the cantilever was 25 rpm, and the rotation speed was 8 rpm;
[0042] (2) Pre-pressing: Take 133 g of the blended raw material, add it into a steel mold with a diameter of 120 mm, place it on the platform of the molding machine, pressurize it to 35 MPa at a rate of 2.5 mm / min, and maintain it for 5 minutes. A rod-shaped pre-pressed blank with a diameter of 120 mm and a height of 5 mm is obtained;
[0043] (3) Sintering: Place the blank into a special PTFE sintering machine equipped with a rotating tray, use air atmosphere, sinter at a temperature of 360°C, for 30 minutes, and a tray speed of 5 rpm;
[0044] (4) Turning: Install a hard stainless steel tool, start and adjust the spindle speed to 3000 rpm, then turn the sintered blank at a feed rate of 0.02 mm / r, with a dwell time of 5 s;
[0045] (5) Drafting and shaping. The processed turning belt with a width of 15 mm, a thickness of 5 mm and a length of about 20 m was flattened, and a section of 500 mm was placed in a constant temperature and humidity chamber, the temperature was set to 80 ° C, the drafting distance was set to 5 mm (1% drafting strain), and it was kept for 60 seconds. After being taken out and cooled, the wollastonite fiber modified polytetrafluoroethylene lubricating material was obtained. The properties of the polytetrafluoroethylene lubricating material are shown in Table 1.
[0046]
[0047] Comparative Example 1
[0048] Raw material components: 950g polytetrafluoroethylene resin (particle size 60μm, tensile strength 35MPa), 50g molybdenum disulfide (size 50μm).
[0049] Preparation process: the same as in Example 1. The properties of the obtained polytetrafluoroethylene lubricating material are shown in Table 2.
[0050] Comparative Example 2
[0051] Raw material components: 650g polytetrafluoroethylene resin (particle size 50μm, tensile strength 40MPa), 300g wollastonite fiber (needle-shaped, thick end diameter 7μm, length 150μm), 50g silicon dioxide (size 0.05μm);
[0052] Preparation process: Same as Example 2. The properties of the polytetrafluoroethylene lubricating material are shown in Table 2.
[0053] Comparative Example 3
[0054] Raw material components: same as Example 2;
[0055] Preparation process: There is no drawing and shaping process, and the rest is the same as in Example 2. The properties of the polytetrafluoroethylene lubricating material are shown in Table 2.
[0056]
[0057] By comparing the examples with the comparative examples, the following conclusions were drawn: (1) When wollastonite fiber was not added to the polytetrafluoroethylene resin matrix, the initial wear rate increased to 9.8×10 -5 mm 3 / N·m, and the heat resistance performance decreased overall, as shown by the tensile strength change rate increasing to -15%, the friction coefficient change rate and the wear rate change rate both increasing to 10%, and the dimensional change also reaching 0.5%; (2) when the wollastonite fiber content increased to 30%, exceeding the agreed range, the tensile strength of the composite material decreased to 17MPa, the friction coefficient increased to 0.23, and the increase in the friction coefficient after thermal aging also reached 0.7%; (3) when the composite material was not subjected to the stretching and shaping treatment, the friction coefficient increased to 0.25, the wear rate increased to 8.9% after thermal aging, and the dimensional change reached 0.3%, all of which could not simultaneously reach the performance range of the material described in the present invention.
[0058] The materials and reagents used in the above examples and comparative examples are all commercially available.
Claims
1. A high heat-resistant and low-friction wollastonite fiber-modified polytetrafluoroethylene lubricating material is prepared by the following raw materials and processes: Raw material components: by weight, 75-89 parts of polytetrafluoroethylene resin, 10-20 parts of wollastonite fiber, and 1-5 parts of lubricating filler; Preparation process: including the following steps: (1) Mechanical blending: placing polytetrafluoroethylene resin, wollastonite fiber and lubricating filler in a mechanical mixer and mixing them evenly to obtain a mixed material; the wollastonite fiber is needle-shaped, with a thick end diameter of 0.5-10 μm and a length of 10-200 μm; the lubricating filler is one or more of molybdenum disulfide, silicon dioxide, graphite, and graphite fluoride, and the size of the lubricating filler is 0.02-80 μm; (2) Pre-pressing: Place the mixed material in a molding machine and press it at a pressure of 35-60 MPa to obtain a pre-pressed blank; (3) Sintering: Sinter the pre-pressed blank in nitrogen or air at 360-380°C for 15-200 min to obtain a sintered blank; (4) Turning: Using hard stainless steel, silicon carbide ceramic or diamond tools to turn the sintered blank to obtain a turning belt; (5) Drawing and shaping: The turned strip is drawn at a temperature of 60 to 120°C and a drawing strain of 0.5 to 5% for 60 to 900 seconds, and after cooling, wollastonite fiber / polytetrafluoroethylene composite lubricating material is obtained.
2. A high heat-resistant and low-friction wollastonite fiber-modified polytetrafluoroethylene lubricating material as claimed in claim 1, characterized in that: Among the raw material components, the particle size of polytetrafluoroethylene resin is 20~80μm and the tensile strength is 25~40MPa.
3. The high heat-resistant and low-friction wollastonite fiber-modified polytetrafluoroethylene lubricating material according to claim 1, characterized in that: The mechanical blending of the preparation process is carried out in a three-axis mixer, the shearing tool speed in the mixing kettle is 5~40rpm, the mixing kettle as a whole revolves around the cantilever at a speed of 10~50rpm, the rotation speed is 2~10rpm, and the mixing time is 3~15min.
4. The high heat-resistant and low-friction wollastonite fiber-modified polytetrafluoroethylene lubricating material according to claim 1, characterized in that: In the pre-pressing of the preparation process, the pressing rate is 0.5~10mm / min, and the holding time is 5~30min; the obtained pre-pressed blank is in a rod shape with a diameter of 10~120mm and a length of 30~500mm.
5. The high heat-resistant and low-friction wollastonite fiber-modified polytetrafluoroethylene lubricating material according to claim 1, characterized in that: The sintering molding of the preparation process is carried out in a special polytetrafluoroethylene sintering furnace equipped with a rotating tray, and the tray rotation speed is controlled to 5~20rpm.
6. The high heat-resistant and low-friction wollastonite fiber-modified polytetrafluoroethylene lubricating material according to claim 1, characterized in that: In the turning process of the preparation process, the feed rate is 0.01~0.05mm / r, the spindle speed is 600~3000rpm, the dwell time is 2~600s; the turning belt thickness is 0.5~15mm.
Citation Information
Patent Citations
Production method of needle-shaped wollastonite modified fluoroethylene resin for sucker rod joints
CN104448636A
Preparation method of multi-orientation polyester fiber
CN114045570A